2013
DOI: 10.1108/09684881311293034
|View full text |Cite
|
Sign up to set email alerts
|

Academic advising: does it really impact student success?

Abstract: Purpose -This study was designed to evaluate academic advising in terms of student needs, expectations, and success rather than through the traditional lens of student satisfaction with the process. Design/methodology/approach -Student participants (n ¼ 611) completed a survey exploring their expectations of and experience with academic advising. Principal axis factor analysis, multiple regression analyses, and analyses of variance were applied to student responses. Findings -Six interpretable factors (i.e. ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 24 publications
5
103
0
Order By: Relevance
“…The researchers viewed that if academic advisor recognize well his role, he can help students navigate academic rules and regulations, help students schedule their courses. This is supported by [11],who examined the association between academic advising and grade point average, they did not observe a statistically significant correlation. On the other side [19]point out the impact of students' advising who attended two or more faculty advising sessions had a grade point average (GPA of 2.0 or higher).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The researchers viewed that if academic advisor recognize well his role, he can help students navigate academic rules and regulations, help students schedule their courses. This is supported by [11],who examined the association between academic advising and grade point average, they did not observe a statistically significant correlation. On the other side [19]point out the impact of students' advising who attended two or more faculty advising sessions had a grade point average (GPA of 2.0 or higher).…”
Section: Discussionsupporting
confidence: 58%
“…Now a day, many researchers investigate the students' opinion about academic advising. [11]surveyed 611 undergraduate students to investigate the relationship between academic advising and students' success or academic performance, the results revealed that academic advising can significantly impact all aspects of a student's academic experience, ranging from advancement of self-efficiency to practical applications of study skills. [12]and [7] notes that effective advisors must appraise each definite student in terms of his needs, interests, skills goals, abilities and adapt their approach to address them properly.…”
Section: {1] Emphasized That the Idea Of Academic Advising Originatedmentioning
confidence: 99%
“…While these differenc es cannot be evaluated quantitatively, they may call into question previous findings that students express more dissatisfaction with academic ad vising than with any other program experienced during their undergraduate careers (Allen & Smith, 2008;Allen, Smith, & Muehleck, 2014;Keup & Stolzenberg, 2004;Kuh et al, 2005) and that satisfaction with academic advising positive ly affects overall satisfaction with the institution (Anderson et al, 2014;Roberts & Styron, 2010;Teasley & Buchanan, 2013;Young-Jones et al, 2013).…”
Section: Build Interpersonal Relationshipsmentioning
confidence: 79%
“…(p. 22) In this excerpt, Drake explained that academic advisors, perhaps more than faculty members and other student affairs professionals, can connect students to the institution. Drake's previous work added to the academic advising literature dis cussing the advisor-advisee relationship (Drake, 2011) and explaining the positive effects of academic advising on student outcomes, includ ing persistence (Elliott & Healy, 2001;Pascarella & Terenzini, 2005;Swecker, Fifolt, & Searby, 2013), satisfaction with the institution (Anderson, Motto, & Bourdeaux, 2014;Roberts & Styron, 2010;Sutton & Sankar, 2011;Teasley & Buchanan, 2013), and overall success (Allen & Smith, 2008;Young-Jones, Burt, Dixon, & Hawthorne, 2013).…”
Section: Student Relationship Management Through Academic Advisingmentioning
confidence: 99%
“…Several studies have stressed the importance of advisors in shaping the career choices of students (Bahr, 2008;Damen & Sulaiman, 2004;Young-Jones, Burt, Dixon, & Hawthorne, 2013), but their low degree of influence on college major decisions in our context indicates a fault line that must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%